Proceedings of the 17th International Conference on Enterprise Information Systems 2015
DOI: 10.5220/0005377701050113
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Usability into the Software Development Process - A Systematic Mapping Study

Abstract: With the increasing use of interactive applications, there is a need for a development with better quality and a good interaction that facilitates the use for end users, because such applications are increasingly present in daily life. Therefore, it is necessary to include usability, which is one of the important quality attributes, in the development process for obtaining good acceptance rates and, consequently, improving the quality of these applications. In this paper we present a Systematic Mapping Study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… Silva et al [34] executed a systematic review where they identified, categorized and summarized technologies that have been used for improve the usability within software development process. For them a technology can be a method, technique, model, tool, approach, and other proposal created by the areas of HCI and SE.…”
Section: B Hci and Software Engneeringmentioning
confidence: 99%
“… Silva et al [34] executed a systematic review where they identified, categorized and summarized technologies that have been used for improve the usability within software development process. For them a technology can be a method, technique, model, tool, approach, and other proposal created by the areas of HCI and SE.…”
Section: B Hci and Software Engneeringmentioning
confidence: 99%
“…With all the identified citations and considering the literature of HCI (for example, [3,11,12]) and existing reviews of HCI approaches that support system development (for example, [4,5,13]), we proposed an initial set of approaches organized in 10 HCI categories. For each HCI category, we included examples of methods, techniques, and standards.…”
Section: Supporting Cmmi-dev With Hci Approachesmentioning
confidence: 99%